MULTIDIMENSIONAL PERSONALITY. THE EPOCH OF THE TRANSFORMATIONS. EDUCATION - Ognevyuk, V. O. (Continuing Professional Education: Theory and Practice, 2019)
In this article are described the variety of transformations and challenges of modern society from the view of philosophy grounds, which lead to dynamic changes in the educational system and as well as preservation and national income accountings to formation or educated person, motivated on selfeducation during whole life; the phenomenon of «multidimensionality of person» is interpreted in civilization context; the problem of expert training in the conditions of modern university education is actualized in this article. The formation of the society of the educated people – is one of the key peculiarities in the XXI centaury. Education can improve the humanity through the formation in personality the inner independence and desire for selfeducation. The main aspect of the education is the development of the moral thinking, the sense of beauty, formation of the kind will. In the teaching and learning process the social experience turns into values, persuasions, knowledge, emotions, motives; the ideals into the person culture; so education becomes the art of the promoting the desire of the multidimensional personality for self development